Views on multilingualism in primary schools, a descriptive enquiry - Pourbaix, Emma; Landuyt, Ingeborg; Ardies, Jan (American Journal of Social Sciences and Humanities, 2023)
Multilingualism is increasingly present in schools due to today’s globalisation. In Western countries pupils often have a mother tongue that is different from the language of instruction at school. Schools and teachers have to deal with this changed situation. This requires a new pedagogical approach, but also a clear vision and new school policies. This research investigates the views on multilingualism that are being held by teachers and staff from 69 Flemish primary schools and which connections can be made between these views and the characteristics of the respondents and their schools. We conducted a survey in which we asked the participants about their school’s school language policy and their own views on multilingualism at school. The results of our analysis indicate that teachers and staff members in primary schools in Flanders (Belgium) still strongly adhere to monolingual policies, especially in the classroom. However, their overall attitude towards multilingualism is slightly less negative than the views of their colleagues in secondary schools. For policymakers, our research puts a finger on a sore spot. It shows that teachers and school authorities still have a long way to go in developing policies that promote language learning. Researchers can find inspiration in this research for a comparative study.